Augmentation of clozapine with amisulpride: an effective therapeutic strategy for violent treatment-resistant schizophrenia patients in a UK high-security hospital. (28th November 2013) - Hotham, James E.; Simpson, Patrick J. D.; Brooman-White, Rosalie S.; Basu, Amlan; Ross, Callum C.; Humphreys, Sharon A.; Larkin, Fintan; Gupta, Nitin; Das, Mrigendra
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Clozapine is used in the management of treatment-resistant schizophrenia and is effective in reducing aggression; however a subgroup of patients is poorly responsive. For violent patients in this group, there is limited literature on the use of strategies to augment clozapine with other agents. Here we present a case series of 6 schizophrenia patients, within a high-security hospital, who have a history of serious violence and who were treated with clozapine augmented with amisulpride. Methods We reviewed case notes and health records for evidence of violence/aggression and positive factors such as engagement in activities, and Clinical Global Impression (CGI) scores were formulated. We also examined metabolic parameters before and after augmentation. Results All 6 of the patients showed clinical improvement in symptoms and a reduction in their risk of violence to others. Five patients had a reduction in number of violent/aggressive incidents, and all patients showed improvement in engagement in occupational, vocational, and/or psychological work. Metabolic parameters were largely unchanged except for 1 patient whose Body Mass Index (BMI) increased. Five patients reported side effects as unchanged or improved. Conclusion These schizophrenia patients with a history of violence showed clinical improvement and reduced aggression and violence with amisulpride augmentation of clozapine. To our knowledge, this is the first report of an antiaggressive benefit of this combination in forensic psychiatric patients. Further studies are warranted to establish the efficacy and anti-aggressive effects of amisulpride augmentation of clozapine.